Sentiment Analysis of Forest Fires on Social Media Networks Twitter Using the Long Short Term Memory (LSTM) Method - Aziz Alfauzi Aziz; Warih Maharani (STMIK Budi Darma, 2023)
The topic of forest fires is of significant interest on social media platforms. In this case, Twitter has been used by 11.8 million users as a means to spread information about forest fires. Twitter, a microblogging service launched on July 13, 2006, allows users to share information for free to themselves and others. Public sentiment related to forest fires can be analyzed through opinions and discussions on Twitter social media. This research aims to analyze the Sentiment of Forest Fires on Twitter Social Networks using the Long Short Term Memory (LSTM) Method. The research data was obtained by crawling the Twitter API using the keyword